Emotional Intelligence And Psychological Well-Being - Fadillah Ismail; Nur Azia Hazida Mohamad Azmi; Chan Shiau Wei (Journal of Social Transformation and Regional Development, 2025)
Emotional intelligence plays a crucial role in managing stress and maintaining mental health, especially in high-stress professions like law enforcement. The purpose of this study is to investigate the relationship between emotional intelligence and psychological well-being among Police Officers in Johor Bahru. 197 officers are selected as sample for this study. Emotional intelligence is measured by using Goleman (2000) that consists of four dimensions which are emotional awareness, emotional management, social emotional awareness and relationship management. Instrument used was Quick Emotional Intelligence Self-Assessment (QEISA) by Mohapel (2013) with 40 items. Besides, psychological well-being is measured by using the 12-item version of the General Health Questionnaire (GHQ-12) (Goldberg, 1972). This variable has divided into two, Component 1 for positive self-esteem and Component 2 for negative self-esteem. This is a quantitative study, and the data collection process is done by distributing a questionnaire and will be analyzed by using Statistical Package for the Social Science (SPSS) version 23.0. Based on the findings, there is a negative moderate relationship between emotional intelligence and psychological well-being among Police Officers, implying that higher emotional intelligence is associated with lower psychological well-being, which suggests the need for targeted interventions to support officers’ mental health.